Perbedaan Nilai Volume Ekspirasi Paksa Detik Pertama (Vep1) Pada Laki - Laki Antara Pekerja Pabrik Dan Pekerja Bukan Pabrik Di Sukoharjo - Riandini, Wilda Al Aluf; , Dr. Sri Wahyu Basuki, M.Kes (2017)
Background: Inhalation of production-related pollution may cause an inflammatic reaction. If the dust exposure continues over time lead to decreased lung function. Decline in lung function occurs because of the pathological changes in the respiratory tract that is characterized by impairment of forced expiratory volume in the first second (FEV1). Impairment FEV1 indicate of obstruction, restriction, or a combination of the respiratory tract. Goals: To determine the difference in forced expiration volume between factory worker and non-factory worker males in Sukoharjo Method: This study is an analytical observational study with a cross-sectional approach and a purposive sampling method. The sample size is 62 males consisting of 31 factory workers and 31 non-factory workers fulfilling the restriction criterias. Spirometer is used as the main instrument. Differences in FEV1 are analyzed with unpaired t-test on the SPSS 23.0 for windows program. Results: Data analysis revealed that p value is 0,013 (p < 0,05). We observed a mean FEV1 of 2,2204 L in factory workers and 2,5752 L in non-factory workers. And the average value including less than the normal value of FEV1 which amounted 3.2 L / min. Conclusion: There is a significant correlation in FEV1 between factory worker and non-factory worker males in Sukoharjo.